2007
DOI: 10.1111/j.1365-2702.2007.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aromatherapy massage with music on the stress and anxiety levels of emergency nurses: comparison between summer and winter

Abstract: High levels of anxiety and stress can be detrimental to the physical and emotional health of emergency nurses and the provision of a support mechanism such as on-site massage as an effective strategy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 32 publications
4
61
0
4
Order By: Relevance
“…Regarding this finding, several other studies have established the positive impact of lavender oil essence on the level of anxiety (19,(27)(28)(29)(30), and these results are consistent with our study. However, a few studies have not demonstrated the same effect (31).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Regarding this finding, several other studies have established the positive impact of lavender oil essence on the level of anxiety (19,(27)(28)(29)(30), and these results are consistent with our study. However, a few studies have not demonstrated the same effect (31).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with the results of Cooke et al (30). They evaluated the effects of three simultaneous interventions (music, massage of extremities, and inhalation aromatherapy) on the stress levels of nurses in an emergency ward over a period of 12 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…En otros estudios, la prevalencia de síntomas de ansiedad es muy superior a la obtenida en nuestro caso. Así, la prevalencia de ansiedad en otras publicaciones varía entre 30.2% (STAI) en enfermeros de oncología (Faria y Maia, 2007) y un 54% en enfermeros del servicio de urgencias (Cooke et al, 2007). Si en nuestro caso analizamos por separado los enfermeros, nuestros resultados siguen mostrando una prevalencia menor de ansiedad (14.8%) que en dichos trabajos.…”
Section: Discusión Y Conclusionesunclassified
“…En estos, se ha observado que entre un 30.2% (STAI) y un 43.3% (HARS) de los profesionales presentaban síntomas de ansiedad y entre un 13 (BDI) y un 44.4% (HDRS), de depresión (Betancourt, Rodríguez, Vallecillo, Sánchez, 2008;Lerma, Rosales, Gallegos, 2009;Pérez, 2006 Por otra parte, un estudio realizado en Turquía en este caso con médicos del servicio de urgencias, arrojaron sínto-mas de ansiedad y depresión (BDI y BAI) en un 14.6% y 15.1% respectivamente (Erdur et al, 2006). En otro trabajo, también realizado en el servicio de urgencias pero en este caso con personal de enfermería, los resultados muestran que un 54% de las personas referían ansiedad moderada o grave (Faces Anxiety Scale) (Cooke, Holzhauser, Jones, Davis, Finucane, 2007).…”
Section: Introductionunclassified
“…Studies found that the olfactory stimulus produces changes in parameters as blood pressure and in skin temperature (3) , it reduces anxiety by massage and aromatherapy in breast cancer patients (4) , reduces anxiety in nurses of emergency team during the winter and summer with massage and aromatherapy (5) and has positive effects in anxiety and self-esteem in elderly woman through massage, aromatherapy and music (6) .…”
Section: Introductionmentioning
confidence: 99%